Penerapan Prinsip Koordinasi dalam Tertibnya Adminsitrasi Kearsipan di Kantor Camat Watang Pulu - Nurhana Ana (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2012)
Abstract The goal of this research is to describe the implementation of coordination principle in order to organize archives' administration at Watang Pulu District Office in Sidenreng Rappang regency, also to determine all factors that affect archives coordination. To meet the goal, this research used these methods to collect data: observation, interview and questionnaires, and through primary data source. The samples were taken from all population, and using descriptive-qualitative analysis method with percentage table to analyse data. Referring to archives coordination principles and implementation's guide-book, the data acquired from questionnaires did not reach 100%, despite archivess storage usage reached a higher 91,1%. Those results showed that coordination process at Watang Pulu district office in Sidenreng Rappang regency has not been fully implemented. While the factors influencing the implementation of archives coordination principle at Watang Pulu district office in Sidenreng Rappang regency are included the not-yet-maximum use of archives storage system, the lack of proper facilities, also the lack of archives knowledgement without further archives training sessions.